Quaid-e-Azam kasa Pakistan Chaty Thay? - "Raza, Dr Hameed Sadique" (Beacon books: Lahore, 1998)
Articles on the political vision of Mahomed Ali Jinnah, 1876-1948 for Pakistan
Keywords: Political and social views